WORDWALL EDUCATIONAL GAMES AND INCREASING STUDENTS' INTRINSIC MOTIVATION IN LEARNING NATURAL SCIENCES IN ELEMENTARY SCHOOL - Fatkhullah; Suryani Sahabuddin, Erma; Hartoto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The objective of this study is to investigate (1) the characterization of Wordwall educational game media usage in the science curriculum for class IV at UPT SPF SD Inpres Kassi, (2) the portrayal of Wordwall educational game media application in the same subject and class, and (3) the impact of Wordwall educational games on students' learning motivation in the science subject for class IV at UPT SPF SD Inpres Kassi, located in Manggala District, Makassar City. This research utilizes a quantitative approach, specifically employing experimental research and a Quasi Experimental Design format known as Nonequivalent Control Group Design. The study's population comprises the students from class IV at UPT SPF SD Inpres Kassi, with a sample of 24 students drawn from classes IV A and IV B through the Purposive Sampling technique. The technique employed for data collection involved both questionnaires and observations. For data analysis, descriptive statistical analysis and inferential statistical analysis were utilized, which included normality tests, homogeneity tests, and hypothesis tests through independent sample T-tests. (1) The utilization of Wordwall educational game media was effectively executed, as indicated by the percentage increase from each meeting, which demonstrated a positive impact supported by observation results; each session progressed from the good category to the very good category. (2) Results from the post-nontest in the experimental group reflected a rise in learning motivation, categorizing it as very high, whereas the control group was classified as high. Although there was an increase, it was not as pronounced as that observed in the experimental class. The Independent Sample T-test's inferential statistical analysis yielded a Sig. (2-tailed) value of 0.001, which is less than 0.05, leading to the rejection of the H0 hypothesis and the acceptance of Ha. (3) This indicates that the implementation of Wordwall educational game media significantly impacts the learning motivation of fourth-grade students in the science subject at SD Inpres Kassi, Manggala District, Makassar City. Therefore, it can be concluded that the use of Wordwall educational game media positively affects the learning motivation of grade IV students at UPT SPF SD Inpres Kassi, Manggala District, Makassar City.